PENGARUH KONSELING KELOMPOK DENGAN TEKNIK SELF-TALK TERHADAP NILAI STOIKISME SISWA DI SMAN PEKANBARU - Sessio Mentiana, Tesa; Umari, Tri; Mardes, Siska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Adolescence, particularly among senior high school students, is often marked by academic pressure, social competition, and peer-related problems that trigger negative emotions such as irritability, anxiety, excessive disappointment, and difficulty accepting failure. Therefore, effective guidance and counseling services are needed to help students improve emotional control, rational thinking patterns, and adaptive coping skills through group counseling services using the self-talk technique. This study aimed to determine the level of students’ stoicism values before and after the implementation of group counseling services using the self-talk technique and examine the effect of the service on improving students’ stoicism values at SMAN Pekanbaru. This research employed a quantitative approach with an experimental research design, namely a Pre-Experimental Design using the One Group Pretest-Posttest Design pattern. The results showed that there was an improvement in students’ stoicism values after receiving group counseling services using the self-talk technique. The Wilcoxon test results indicated a significant difference between the pretest and posttest scores, with an Asymp. Sig. (2-tailed) value of 0.008, while the N-Gain test results showed an increase with an average N-Gain score of 0.79, which was categorized as high. Therefore, group counseling services using the self-talk technique proved effective in improving students’ stoicism values at SMAN Pekanbaru.